Prognostic and predictive value of pre-treatment blood-based inflammatory biomarkers in patients with urothelial carcinoma treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Széles, Ádám; Kubik, András; Váncsa, Szilárd; Grünwald, Viktor; Hadaschik, Boris; Ács, Nándor; Hegyi, Péter; Nyirády, Péter; Szarvas, Tibor (Frontiers in Immunology, 2025)
Background and objectivesThe therapeutic landscape of locally advanced or metastatic urothelial carcinoma (mUC) is rapidly evolving, and immune checkpoint inhibitors (ICI) have become an integral part of the standard therapy. However, the majority of patients do not benefit from this treatment. Hence, finding prognostic and predictive biomarkers may improve therapeutic decision-making. The aim of this study was to analyze the prognostic and predictive significance of liquid biomarkers (NLR, CRP, PLR, and LDH) in mUC patients treated with ICI.MethodsWe collected articles from PubMed, Cochrane, and Embase databases with primary outcomes of overall survival (OS), progression-free survival (PFS) and objective response rate (ORR).Key findings and limitationsWe compiled data from a total of 6,673 ICI-treated patients with locally advanced or mUC from 31 articles. Pooled univariate analysis demonstrated that high pre-treatment NLR is significantly associated with worse OS (HR: 2.19; 95% CI: 1.80-2.68) and PFS (HR: 1.90; 95% CI: 1.57-2.31). Similarly, elevated CRP levels were associated with worse OS (HR: 1.75; 95% CI: 1.37-2.24) and PFS (HR: 1.58; 95% CI: 1.26-1.99).Conclusions and clinical implicationsElevated pre-treatment NLR, CRP, PLR, and LDH are significantly associated with worse OS and PFS in ICI-treated urothelial carcinoma patients, suggesting that they have potential prognostic and predictive value in treatment decisions.Patient summaryIn this systematic review and meta-analysis we summarized the existing data on inflammatory laboratory biomarkers and their potential impact on immunotherapy outcomes in urothelial cancers.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42022291449.